Arabidopsis 14-3-3 Proteins: Fascinating and Less Fascinating Aspects - Jaspert, Nina; Throm, Christian; Oecking, Claudia (Frontiers in Plant Science, 2011)
14-3-3 dimers are well known to interact with diverse target proteins throughout eukaryotes. Most notably, association of 14-3-3s commonly requires phosphorylation of a serine or threonine residue within a specific sequence motif of the client protein. Studies with a focus on individual target proteins have unequivocally demonstrated 14-3-3s to be the crucial factors modifying the client’s activity state upon phosphorylation and, thus, finishing the job initiated by a kinase. In this respect, a recent in-depth analysis of the rice transcription factor FLOWERING LOCUS D1 (OsFD1) revealed 14-3-3s to be essential players in floral induction. However, such fascinating discoveries can often be ascribed to the random identification of 14-3-3 as an interaction partner of the favorite protein. In contrast, our understanding of 14-3-3 function in higher organisms is frustratingly limited, mainly due to an overwhelming spectrum of putative targets in combination with the existence of a multigene 14-3-3 family. In this review we will discuss our current understanding of the function of plant 14-3-3 proteins, taking into account surveys of the Arabidopsis 14-3-3 interactome.